Comparison of Two Approaches to Enhance Self-Esteem and Self-Acceptance in Chinese College Students: Psychoeducational Lecture vs. Group Intervention - Qian, Yi; Yu, Xinnian; Liu, Fulian (Frontiers in Psychology, 2022)
Objective Self-esteem and self-acceptance are not only basic features but also influential factors of mental health. The present study aimed at assessing the effects of psychoeducational lecture and group intervention on self-esteem and self-acceptance in Chinese college students. Methods A total of 149 Chinese college students who participated in a mental health course were randomly class-based assigned into the psychoeducational lecture group (n = 62) and the self-focused intervention group (n = 87). The lecture group received 6-session psychoeducational lectures on overview of mental health, campus adaptation, stress adjustment, self-understanding, emotion management, and interpersonal relationships. The self-focused intervention group was treated with self-related group activities involving aspects of self-knowledge, self-feeling, and self-regulation for six sessions. Pre- and post-intervention measurements were taken with Rosenberg Self-Esteem Scale and Self-Acceptance Questionnaire for both groups. Results Self-esteem significantly increased in both groups after six sessions. However, the enhancement of self-acceptance was more robust for the self-focused intervention group than the psychoeducational lecture group. Conclusion The psychoeducational lecture and self-focused intervention were effective approaches to improve self-esteem for Chinese college students. With respect to self-acceptance, self-focused group intervention might have a more prominent effect.